2018
DOI: 10.3748/wjg.v24.i15.1632
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection for early esophageal neoplasms using the stag beetle knife

Abstract: AIMTo determine short- and long-term outcomes of endoscopic submucosal dissection (ESD) using the stag beetle (SB) knife, a scissor-shaped device.METHODSSeventy consecutive patients with 96 early esophageal neoplasms, who underwent ESD using a SB knife at Kure Medical Center and Chugoku Cancer Center, Japan, between April 2010 and August 2016, were retrospectively evaluated. Clinicopathological characteristics of lesions and procedural adverse events were assessed. Therapeutic success was evaluated on the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Tsuji et al reported that the 3- and 5-year cumulative metachronous cancer rates were 9.9% and 24.5%, respectively [ 40 ]. Kuwai et al reported that the 3- and 5-year cumulative metachronous cancer rates were 14% and 26%, respectively [ 41 ]. The metachronous cancer rates are considerably high and surveillance endoscopy should be performed carefully.…”
Section: Cumulative Metachronous Cancer Rate After Esophageal Esdmentioning
confidence: 99%
“…Tsuji et al reported that the 3- and 5-year cumulative metachronous cancer rates were 9.9% and 24.5%, respectively [ 40 ]. Kuwai et al reported that the 3- and 5-year cumulative metachronous cancer rates were 14% and 26%, respectively [ 41 ]. The metachronous cancer rates are considerably high and surveillance endoscopy should be performed carefully.…”
Section: Cumulative Metachronous Cancer Rate After Esophageal Esdmentioning
confidence: 99%
“…– Advantages: Ability to grasp away from the submucosal plane and check position before cutting improves safety, good for more technically challenging anatomy for example, oesophagus and colorectal as well as gastric. 11 16 …”
Section: Knivesmentioning
confidence: 99%
“…There are a number of scissor-type cutting and coagulation devices emerging that may be helpful. For the stomach, we routinely use the i-knife and in some cases will also employ the SB knife[141]. This device can both coagulate and cut tissue using a scissor motion.…”
Section: Early Gastric Cancer and Submucosal Tumors (Smts) Of The Stomentioning
confidence: 99%